Spatial distribution of Rastrococcus invadens Williams (Hom., Pseudococcidae) in mango trees - Boavida, C.; Neuenschwander, Peter; Schulthess, F. (1992)
The spatial dispersion pattern and the intracanopy distribution of the mango mealybug, Rastrococcus invadens Williams, were assessed during one year in a small mango plantation, in order to develop sampling plans and facilitate sampling in mango trees. Mean number of mango mealybugs per leaf differed significantly between trees for most sampling dates, between old and young leaves, and between geographical quadrants. A second one‐time assessment of the intracanopy distribution of the mango mealybugs was made in two infested trees. Significant differences among quadrants, but not between old and young leaves, nor between top and bottom of the trees were found. In general, these differences were inconsistent, and the only stratification of samples recommended is the one between age classes of leaves.Because of an almost total overlap of generations, the number of females corresponded closely to the one of the total population. To analyse the dispersion pattern of the mango mealybug, Taylor's power law was applied to the sampling data. The index of aggregation didn't change significantly with season. On this basis, a common index of aggregation was calculated, which was incorporated into Wilson & Room's and Karandino's equations to develop enumerative and binomial sampling plans.